Blood loss and cost-effectiveness of oral vs intravenous tranexamic acid in primary total hip arthroplasty: A randomized clinical trial. Issue 171 (November 2018) - Wu, Yuangang; Zeng, Yi; Hu, Qinsheng; Li, Mingyang; Bao, Xianchao; Zhong, Jian; Shen, Bin
Abstract: Background: To assess the blood loss and cost-effectiveness of the oral and intravenous (IV) administration of tranexamic acid (TXA) for the treatment of primary total hip arthroplasty (THA). Methods: From January 2017 to August 2017, 100 patients undergoing primary THA were enrolled and randomly divided into two groups. In the oral TXA group (N = 50), 1 g of TXA (2 tablets of 500 mg) was given 2 h before the incision, and the same dose was repeated 3 h and 6 h postoperatively. In the IV TXA group (N = 50), 1 g of TXA was administered 10 min before the incision, and the same dose was repeated 3 h and 6 h postoperatively. The total follow-up period was 6 months. Results: There were no statistically significant differences in total blood loss (863.3 ± 272.5 mL and 886.1 ± 200.2 mL, P = 0.66), maximum Hb drop (2.9 ± 0.6 g/dl and 3.1 ± 0.8 g/dl, P = 0.17), maximum Hct drop (7.4 ± 2.1% and 7.7 ± 1.8%, P = 0.48), transfusion rates (1 and 2, P = 1.00) and transfusion units (1.5 u and 3 u, P = 0.56) between the two groups. However, the costs of TXA in the oral group were significantly lower than those in the IV TXA group (¥600 and ¥3150, P < 0.01). There was no difference in the Hb levels on postoperative days 1 and 3. No significant differences were found for operating time, hospital length of stay, DVT and/or PE, and wound complications in the postoperative follow-up. Conclusions: The study demonstrated that the oral and IV administration of TXA in patients undergoing THA was proved to be an equivalent and effective method in reducing blood loss and transfusion rates. However, oral TXA is more cost-effectiveness than IV TXA, and it may be an alternative to the IV form. Highlights: We compared the efficacy of oral and IV TXA in primary THA. Oral and IV administration of TXA appears to be associated with similar benefits. Oral TXA may be more cost-effectiveness than IV TXA.